NiCo2O4-graphene nanocomposites in sugar industry wastewater fed microbial electrolysis cell for enhanced biohydrogen production. (July 2020) - Jayabalan, Tamilmani; Manickam, Matheswaran; Naina Mohamed, Samsudeen
Abstract: Hydrogen energy from real-time effluents by Microbial Electrolysis Cell (MEC) has gained intense research interests. Especially, material development for both electrodes and catalysts not only influence the performance but also the overall process economy. In this study, the cathode employed was Nickel foam (NF) modified with synthesized catalyst of NiCo2 O4 -graphene nanocomposites in MEC operated with sugar industry wastewater. NiCo2 O4 -graphene nanocomposites decorated NF exhibited an excellent performance in terms of hydrogen production rate 0.14 ± 0.003 L/L D −1, which was 3.2 times higher than control NF at the optimized conditions. Electrochemical Impedance Spectroscopy reflected the improved catalytic performance of the nanocomposites 1.6-fold enhancement over control. The improved performance was reported as Coloumbic efficiency 66.2%, Cathodic hydrogen recovery 27.9%, Overall hydrogen recovery 18.4% and COD removal efficiency 58.1% respectively. Hence, suitability of novel catalyst was investigated demonstrating better results of modified cathode with bio-catalyzed anode employed in industrial effluent. Graphical abstract: Image 1 Highlights: NiCo2 O4 . rGO and NiCo2 O4 were synthesized and used as a catalyst in the cathode of MEC. Nanocomposite's electrochemical and structural Characterizations revealed higher catalytic activity. NiCo2 O4 . rGO showed the hydrogen production rate of 3.2 times higher than control NF. Improved MEC performance and hydrogen recoveries are achieved with the novel catalyst.